Undescended Testis in Benghazi Children Hospital: A Retrospective Study of Correlation Between Age at Presentation, Laterality, Presence of Hernial Sac, and Testicular Size from 2020 to 2024 - Ahmed Abdulmawlay, Dr. Rabeeah; Asst. Prof. Saleh Algumati (Benghazi University Medical Journal, 2026)
Background: The inability of the testis to descend into its typical scrotal position at birth is known as undescended testis (UDT) or cryptorchidism. It is estimated that one to four percent of full-term and up to forty-five percent of preterm newborn male neonates are affected by UDT. Objective: To determine the mean age of patients at the time of presentation with palpable undescended testis, to analyze the distribution of cases by laterality (right, left, or bilateral), to assess the association between undescended testis and the presence of a hernial sac, to evaluate the size of the affected testis in comparison with the contralateral normal testis, and to examine the correlations among these variables in order to provide evidence-based clinical recommendations. Methods: A hospital-based retrospective study was conducted in the Pediatric Surgery Department at Benghazi Children Hospital, encompassing all male patients who underwent surgery for a confirmed diagnosis of undescended testis, aged between five months and 12 years, from 2020 to 2024. All patient records were reviewed to extract the required data. Results and conclusion: This is a retrospective review of 140 children (UDT) presenting to Benghazi Children's Hospital to evaluate the age of presentation, laterality, size of the testis, the presence of hernial sac, and the associated surgical findings. The majority of the patients (67.9%) presented between 0 and 2 years, which is very much in accordance with international guidelines of early surgical intervention and presentation. However, a notable proportion (32.1%) presented after the age of 3, suggesting a delay in referral and time of operation. Increased risk of testicular atrophy with increasing age was noted, particularly in the 6–8year-old group. The presence of hernial sac was observed in 35.7% of the instances, more in the younger age group of children. Laterality was evenly split between the right and left sides, with bilateral cases constituting only 5%, Nearly every patient who had a history of empty scrotum was admitted for orchidopexy. Two patients who had previously undescended testes (UDT) and a history of recurrent irreducible hernias were admitted for herniotomy. Three cases of testicular torsion and one case of irreducible inguinal hernia were among the four patients who were brought as emergencies and had a history of inguinal swelling. No statistically significant correlations were noted between testicular size and age, laterality, or the presence of a hernia.